2011
DOI: 10.1016/j.jaac.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Decision Making in Depressed Adolescents: A Functional Magnetic Resonance Imaging Study

Abstract: Objective Despite evidence that impaired reward- and risk-related behavior during adolescence can have potentially serious short- and long-term consequences, few studies have investigated the impact of depression on reward-related selection in adolescents. This study examined the relationship between reward-related behavior and prefrontal activations in depressed and healthy adolescents during a decision-making task. Method Twenty-two adolescents with no personal or family history of psychiatric illness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 43 publications
4
32
1
Order By: Relevance
“…Reward system abnormalities have also been found both in adult (81) and adolescent populations with MDD (82), leading to a characterization of “ hypo-sensitivity to rewards ” in MDD, with hypo-activation in VS/PVC (83, 84). In fact, a recent study with adolescents with MDD found reduced reward-related activity in the right caudal ACC, caudate, and OFC during high risk-high gain trials (85). Similarly, (82) found decreased activation in the caudate and inferior OFC during both reward anticipation and response in 9–17 years old with MDD.…”
Section: Current Research On Pvc Disruption In Mood Disordersmentioning
confidence: 99%
“…Reward system abnormalities have also been found both in adult (81) and adolescent populations with MDD (82), leading to a characterization of “ hypo-sensitivity to rewards ” in MDD, with hypo-activation in VS/PVC (83, 84). In fact, a recent study with adolescents with MDD found reduced reward-related activity in the right caudal ACC, caudate, and OFC during high risk-high gain trials (85). Similarly, (82) found decreased activation in the caudate and inferior OFC during both reward anticipation and response in 9–17 years old with MDD.…”
Section: Current Research On Pvc Disruption In Mood Disordersmentioning
confidence: 99%
“…and reward. 68 Reward-related decision-making was examined within a longitudinal study of 221 11-yearold boys, 25 of whom had a depressive disorder at age 10 or 11. 69 Participants completed a behavioral decisionmaking task called the reward-contingent decision (RCD) paradigm 70,71 (see Table 2) which involves reward-related decisions under conditions of uncertainty and is considered to be emotional in nature.…”
Section: Comorbid Depression May Contribute To Decision-making Impairmentioning
confidence: 99%
“…After high-magnitude rewards, those with depression exhibited a greater response than control participants in the amygdala bilaterally and the inferior OFC. 76 In another neuroimaging study using fMRI, 68 22 adolescents with no personal or family history of psychiatric illness and 22 adolescents with MDD were administered a two-choice decision-making task involving probabilistic monetary rewards with varying levels of risk: the Wheel of Fortune. 77 During risky decision-making, healthy adolescents used the brain regions involved in inhibitory control (right lateral OFC), whereas depressed adolescents engaged areas involved in conflict monitoring (right caudal ACC).…”
Section: Comorbid Depression May Contribute To Decision-making Impairmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, neuroimaging studies of adolescent MDD have examined reward processing in the context of monetary reward. These studies have predominantly reported diminished striatal response during the anticipation and receipt of reward in adolescents with MDD (Forbes et al, 2010; Olino et al, 2011; Shad et al, 2011). Given that emotional facial expressions are socially relevant stimuli and that positive (i.e., happy) emotional facial expressions are perceived as cues of potential social reward in adolescents, it is therefore possible that happy face stimuli would be associated with alterations in neural systems supporting social-affective processing and the regulation of social-affective processes, in adolescents with mood disorders.…”
Section: Introductionmentioning
confidence: 99%